Equality of Google scholar with web of science citations: case of Malaysian engineering highly cited papers - Ale Ebrahim, N.; Salehi, H.; Embi, M.A.; Danaee, M.; Mohammadjafari, M.; Zavvari, A.; Shakiba, M.; Shahbazi-Moghadam, M. (Canadian Center of Science and Education, 2014)
This study uses citation analysis from two citation tracking databases, Google Scholar (GS) and ISI Web of Science, in order to test the correlation between them and examine the effect of the number of paper versions on citations. The data were retrieved from the Essential Science Indicators and Google Scholar for 101 highly cited papers from Malaysia in the field of engineering. An equation for estimating the citation in ISI based on Google scholar is offered. The results show a significant and positive relationship between both citation in Google Scholar and ISI Web of Science with the number of versions. This relationship is higher between versions and ISI citations (r = 0.395, p<0.01) than between versions and Google Scholar citations (r = 0.315, p<0.01). Free access to data provided by Google Scholar and the correlation to get ISI citation which is costly, allow more transparency in tenure reviews, funding agency and other science policy, to count citations and analyze scholars' performance more precisely.